2018
DOI: 10.1177/1071100718772041
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship of Plantar Fascia Thickness and Preoperative Pain, Function, and Quality of Life in Recalcitrant Plantar Fasciitis

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…On magnetic resonance imaging (MRI) findings, the mean thickness of the plantar fascia of healthy feet was 3.1 mm ± 1.0, while it was 4.4 mm ± 1.6 for the affected feet. Furthermore, Gamba et al used ultrasound and MRI to identify a correlation between the thickness of plantar fascia and pain 31 . They found that the thickness of the plantar fascia in patients with PF did not correlate with pain using a VAS 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On magnetic resonance imaging (MRI) findings, the mean thickness of the plantar fascia of healthy feet was 3.1 mm ± 1.0, while it was 4.4 mm ± 1.6 for the affected feet. Furthermore, Gamba et al used ultrasound and MRI to identify a correlation between the thickness of plantar fascia and pain 31 . They found that the thickness of the plantar fascia in patients with PF did not correlate with pain using a VAS 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Gamba et al used ultrasound and MRI to identify a correlation between the thickness of plantar fascia and pain 31 . They found that the thickness of the plantar fascia in patients with PF did not correlate with pain using a VAS 31 . The findings from this study probably reflect a relationship that does not correlate with the thickness of the plantar fascia and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mahowald et al 18 found a correlation between plantar fascia thickness and symptoms of plantar fasciitis, in that thickness changes could be used to objectively measure the effectiveness of various treatments. However, a study by Gamba et al 11 found no relationship between plantar fascia thickness and negative clinical markers (ie, pain, function, and patient surveys) associated with plantar fasciitis. This may serve to change how we should view plantar fascia thickness and how it relates to gender.…”
Section: Plantar Fascia Thickness and Plantar Fasciitismentioning
confidence: 97%
“…There are numerous treatment modalities that have been used to treat plantar fasciitis (PF), but the condition generally returns during life and can impair gait [7]. While pain is indicative of PF, the thickness, when measured 0.5 cm from the calcaneus insertion of the plantar fascia, is normally 0.4 mm or less in healthy individuals and greater than 0.4 mm in individuals with PF [8,9].…”
Section: Introductionmentioning
confidence: 99%